2011
DOI: 10.1107/s0021889811036910
|View full text |Cite
|
Sign up to set email alerts
|

Potential thermal expansion of calcitic and dolomitic marbles from Andalusia (Spain)

Abstract: Marble has historically been used as an ornamental stone because of its aesthetic appeal, ease of polishing and ex;cellent physical properties. One of the main factors affecting the durability of marbles is their thermal behaviour. Although marble is used extensively in Spain as a building and decorative material, little research has been done into its thermal behaviour. In this work, the textural and microstructural properties of seven calcitic and dolomitic marbles from Andalusia (southern Spain) were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 40 publications
(40 reference statements)
0
5
0
2
Order By: Relevance
“…Table 7 shows that the calcschist and marble contain 98% and 99% fully recrystallized calcite and dolomite minerals, respectively. From the literature it is known that calcite minerals possess relatively high thermal expansion coefficients, parallel to the crystallographic c-axis, of 24-29 × 10 −6 K −1 [42][43][44]. A study aiming at calcitic and dolomitic marbles from Andalusia (Spain) reported averaged linear thermal expansion coefficients, measured between 20-90 • C, of 11 × 10 −6 K −1 for both types of marbles [43].…”
Section: Temperature Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 7 shows that the calcschist and marble contain 98% and 99% fully recrystallized calcite and dolomite minerals, respectively. From the literature it is known that calcite minerals possess relatively high thermal expansion coefficients, parallel to the crystallographic c-axis, of 24-29 × 10 −6 K −1 [42][43][44]. A study aiming at calcitic and dolomitic marbles from Andalusia (Spain) reported averaged linear thermal expansion coefficients, measured between 20-90 • C, of 11 × 10 −6 K −1 for both types of marbles [43].…”
Section: Temperature Effectmentioning
confidence: 99%
“…From the literature it is known that calcite minerals possess relatively high thermal expansion coefficients, parallel to the crystallographic c-axis, of 24-29 × 10 −6 K −1 [42][43][44]. A study aiming at calcitic and dolomitic marbles from Andalusia (Spain) reported averaged linear thermal expansion coefficients, measured between 20-90 • C, of 11 × 10 −6 K −1 for both types of marbles [43]. On average, these are somewhat higher than reported mean expansion coefficients, assessed in a range of 20-100 • C, for sandstones and limestones of 10 and 8 × 10 −6 K −1 , respectively [45].…”
Section: Temperature Effectmentioning
confidence: 99%
“…This geological process is associated with another climate process that also contributes to generating such debris by the mechanical breakdown of the rock, promoting brecciation, disintegration, and the formation of dolomitic sands. Frost shattering [ 22 ] and the thermal expansion of these rocks at high temperatures [ 23 ] appear to be the dominant local weathering processes. These features lead to strong edaphical stress and prevent the surrounding vegetation, usually conifer forests, from succession and closure.…”
Section: Definition Of the Dolomite Phenomenonmentioning
confidence: 99%
“…In addition to external environmental factors, the material properties of marbles have a significant impact with respect to the decay phenomena (e.g. Weiss 2002a; Zeisig et al 2002;Koch and Siegesmund 2004;Scheffzück et al 2007;Sáez-Pérez and Rodrígue-Gordillo 2009;Luque et al 2011;Shushakova et al 2013;Menningen et al 2018a, b). The weathering of marble is usually a slow geological process, but fast enough for monuments to become damaged in less than a decade.…”
Section: Introductionmentioning
confidence: 99%